Water Regimes effect on the growth and antioxidant content of purslane (Portulaca Oleracea L.) - Su, Ging Sam (2016)
A pot experiment was conducted at the rain shelter and laboratory in the Faculty of Sustainable Agriculture, Universiti Malaysia Sabah Sandakan Campus to investigate the effect of different water regimes on the growth, antioxidant content, and carbon, hydrogen and nitrogen content of purslane (Portulaca oleracea L.). The soil media used had soil organic matter content of 22.02%, electrical conductivity (EC) 1.15 dS m-1 and pH 5.23. The experimental design was Completely Random Design using five treatments namely continuous field capacity condition, continuous saturated condition, continuous flooded condition, flooded 10 days followed by saturated condition, and saturated 10 days followed by field capacity condition with 5 replications. The data on the plant height, leaf length, leaf width, stem diameter, internode length, shoot moisture content, relative leaf water content, total phenolic content, total flavonoid content, ash content, carbon, hydrogen and nitrogen content, and crude protein content were collected after 20 days of treatment application. Results were analyzed by ANOVA using SPSS program and treatment means were compared using LSD test at the 5% probability level. The results revealed that effects of different water regimes on plant height, leaf length, leaf width, stem diameter, total phenolic content, total flavonoid content, ash content, hydrogen content, nitrogen content, and crude protein content in purslane were significant. However, there were no significant effects of different water regimes on internode length, leaf relative water content, shoot water content, and carbon content in purslane. Field capacity condition had produced purslane with longest internode length (76mm), highest leaf relative water content (79.85%), highest total phenolic content (3.06 mg GAE/g), and highest ash content (17.5%). Continuous saturated condition produced purslane with highest plant height (429.0mm), and highest shoot water content (90.59%). Continuous flooded condition produced purslane with longest leaf (26.3mm), widest leaf(14mm), highest total flavonoid content (1.35 mg QE/g), highest carbon(40.3%), hydrogen(6.14%), nitrogen (3.14%) and crude protein content (19.62%). It may be recommended as a water saving technology for the water scarce areas for purslane production.